¿Listos para qué? Alistamiento versus Readiness (Journal of the Spanish Institute for Strategic Studies, 2023)
The fundamental purpose of Armed Forces is to fight and win a Nation’s conflicts. Therefore, it is critical that Ministers of Defense (MoD) continually assesses warfighting readiness and capabilities. Readiness is the ability of Armed Forces to conduct and successfully accomplish assigned missions as specified in the National Military Strategy (NMS) with sufficient and sustainable capabilities resulting from personnel, equipment, training, and supporting infrastructures.The readiness system provides an overall assessment of the Ministry of Defense’s (MoD) ability to execute the NMS and captures the overarching readiness for each level of warfighting. History holds numerous examples of the cost nations have paid when their Armed Forces were not prepared to respond.Next, the concept of International Readiness is shown, its extrapolation to the Spanish environment and some examples of Readiness systems implemented in other countries are analyzed. This article concludes with the future challenges that are presented to these Readiness evaluation systems in the coming years.